Intention of Social Entrepreneurship in Muslim Communities in Cirebon - Kurjono, Kurjono; Syafitri, Syafitri; Abdullah, Abdullah; Kamil, Anton Abdulbasa (Perhimpunan Intelektual Muslim Indonesia, 2024)
The purpose of this study is to examine students' entrepreneurial intentions within the Muslim community and analyze gender differences. The overarching theory utilized is the Theory of Planned Behavior. The study involves 270 Islamic boarding school students in Cirebon. The questionnaire comprised four sections aimed at gathering information about behavioral attitudes, subjective norms, perceived control over behavior, and entrepreneurial intentions. Responses were recorded on a five-point numeric scale. The findings revealed that attitudes toward behavior and subjective norms were the primary predictors of entrepreneurial intentions, whereas perceived behavioral control was not significant. Additionally, the study found no notable difference in social entrepreneurship intentions between male and female students. The limitations of this study are attributed to the sample size and specific focus on Islamic boarding school students in Cirebon. Further research is recommended to predict social entrepreneurial intentions among a larger cohort of Islamic boarding school students by incorporating practical business activities. This study underscores the importance of integrating entrepreneurship education into the curriculum of Islamic boarding schools in Indonesia.